An assessment of mobility limitations of the physically disabled in Nairobi: a case study of trip to CBD - Nyangueso, Samuel Ouma (My University, 2006)
Accessibility however necessary and desirable to all; physical abilities, socioeconomic characteristics and external environment may make it difficult for the disabled to overcome physical separations of opportunity areas through transport. Ever since mobility limitations in transport systems for the disabled came to the limelight early last century, it has been of great concern to the world community. The limitations deny the disabled equal access to transport , one of the transport challenges that have faced both developed and developing countries. Many international and national bodies, governments and other institutions are putting in place initiatives aimed at removing mobility barriers for the disabled. United Nations in 1994 did not only identify accessibility as the first area to equalization of opportunities for Persons with Disabilities, but also crafted a rule committing all countries to initiate measures that guarantee them access to public transport services and other means of transportation, streets and other outdoor environments. Kenya on her part enacted Persons with Disabilities law in 2003, which treats accessibility and mobility for the disabled as rights and entitled them to a barrier-free and disability-friendly environment. The purpose of the study was to establish mobility limitations for the physically disabled in Nairobi and recommend measures that may enhance their mobility. In doing so, the study also sought to: (i) determine the travel characteristics for the disabled; and (ii) investigate necessity of mobility to the disabled population in Nairobi. A total of 53 subjects were sampled from a sample frame of 498 for administration of personal questionnaire. Other primary and secondary data sources were used as well as relevant literature reviewed. Qualitative and quantitative analysis techniques were applied in obtaining the results. The study found out that regular mobility for the disabled in Nairobi was prerequisite for securing their livelihood. Their travel characteristics were basically influenced by their places of residence and their sources of livelihoods. The disabled were found to iv be public transport captives over long distances and either walk or use manual mcycies or wheelchairs for mobility and accessibility over short distances. They, however, experience mobility limitations throughout their trips to their finai destinations. The structural design and operation of public service vehicles; the roads and terminal facilities; as well as the pubic attitude have inherent limitations that prevent or discourage their mobility by both public tr of transport. The interventions recommended include gradual introduction of suitably adapted public service vehicles for the disabled; enhancing inter-modal interface and provisions of sheltered-seats at the terminals; road widening and segregation of cycle paths; provisions for road furniture and transfer facilities; and guaranteed safe crossings. Besides, improving education for the disabled; decentralization of employment sites; and change in transport institutional framework were recommended.